Trinitarian Theology After and with—but Not Against—Aquinas? - McCurry, Jeffrey (Modern theology, 2005)
Gilles Emery, Trinity in Aquinas, O.P. (Ypsilanti, Michigan: Sapientia Press, 2003), ix +361 pp. Matthew Levering, Scripture and Metaphysics: Aquinas and the Renewal of Trinitarian Theology (Malden, Massa-chusetts: Blackwell, 2004), x +254 pp Timothy L. Smith, Thomas Aquinas' Trinitarian Theology: A Study in Theological Method (Washington, D.C.: Catholic University of America Press, 2003), xiii +258 pp.